The Influence of Organizational Culture and Work Discipline on Employee Performance at Pt Infomedia Medan - Halimatussa' diah (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of Organizational Culture and Work Discipline on Employee Performance at PT Infomedia Medan. Research using quantitative methods, processing primary data so that it gets a phenomenon. Data in the field was collected by interviewing and distributing questionnaires to employees of PT. Infomedia Medan is a population of 43 people. The method of data analysis in the study used Multiple Linear Regression with SPSS 19.00 software. The results of the study stated that Organizational Culture had no effect on the performance of PT Infomedia Medan's employees. This can be seen from the multiple linear regression analysis through the t test which is negative with a t-count of -0.659 with sig. 0.514. The magnitude of the influence of Organizational Culture on Employee Performance of -0.063 units. Whereas Work Discipline has a positive and significant effect on the performance of employees of PT Infomedia Medan. This can be seen from the multiple linear regression analysis through tests that are positive with a tcount of 5.110 with sig. 0.000. The magnitude of the influence of Work Discipline on Employee Performance of 0.706 units